The Aesthetic of life’s cycle: a Kantian analysis of figurative language in William Blake’s The Ecchoing Green - Ochia, Li; Omboy, Aira Bea; Monteza, Ana Mae (Leksika: Jurnal Bahasa, Sastra dan Pengajarannya, 2025)
The study explored the aesthetic portrayal of life’s cyclical nature in William Blake’s poem, The Ecchoing Green. In particular, it focused on analyzing the role of figurative language in enhancing the poem’s artistic depth. In pursuit of this objective, the study employed a qualitative descriptive method and aesthetic criticism. Grounded on Immanuel Kant’s Analytic of the Beautiful, the study analyzed how Blake’s use of literary devices evoked the four principles central to aesthetic judgment: disinterested pleasure, universal subjectivity, purposiveness and necessity. To capture the representation of each stage of life, the analysis categorized the figurative expressions according to the three fundamental stages of life: childhood, adulthood and old age. The findings revealed that the use of figurative language not only delineates the phases of life. It is evident that the poem did not solely illustrate the joys and innocence of youth, the wisdom and resilience of adulthood and the introspective peace of old age. Through the aesthetic lens, it revealed how figurative language captured the essence of each stage of life. Significantly, the figurative languages in The Ecchoing Green enhanced the poem’s artistic coherence and emotional resonance. This study showed how the harmonious structure and universal themes embedded in the poem evoked a deep appreciation of the transient yet beautiful nature of human life. Ultimately, the research highlighted the role of figurative language in shaping aesthetic experience and literary perception. As a result, the analysis contributed to a richer understanding of how language evoked deeper philosophical and universal truths. More importantly, the study strategically contributed to the promotion of literary appreciation and critical thinking. In the light of the study’s insights, the analysis encouraged active engagement with literature as a medium for understanding human experiences across life stages. By fostering a deeper literary appreciation, cultural awareness and critical thinking, the study aligned with Sustainable Goal 4 which is the Quality Education.